The Effect of Cowpeas (Vigna Unguiculata) Addition on the Organoleptic Quality, Protein Content, and Fat of Buffalo Milk Ice Cream - Rafhael Iman Anugrah Sitepu; Nurzainah Ginting; Basta Simanullang (Talenta Publisher, 2026)
This study aimed to determine the effect of cowpeas (Vigna unguiculata) addition on the organoleptic quality, protein content, and fat content of buffalo milk ice cream. This study was conducted using a Completely Randomized Design (CRD) with four treatments: P0 (0%), P1 (10%), P2 (20%), and P3 (30%), each with five replications. Observed parameters included organoleptic quality (color, aroma, taste, and texture), as well as the protein and fat content of the ice cream. hedonic data were analyzed using the Kruskal–Wallis test, while chemical data were analyzed using ANOVA. The results showed that the addition of cowpeas extract had a significant effect (p < 0.05) on color, aroma, and taste, but not on texture. The best treatment was by addition 30% cowpeas. Furthermore, P3 produced the lowest fat content at 4.38% and the highest protein content at 6.08%. It can be concluded that the addition of cowpeas up to 30% improves the nutritional value of buffalo milk ice cream.